2001
DOI: 10.3354/dao044149
|View full text |Cite
|
Sign up to set email alerts
|

Increase in number and size of kidney concretions as a result of PCP exposure in the freshwater snail Planorbarius corneus (Gastropoda, Pulmonata)

Abstract: Molluscan kidneys are able to excrete solids in the urine in the form of concretions. It is thought that increased formation of these concretions occur under pollutant, environmentally or reproductive induced stress. This study examined the formation of concretions in the kidney of the freshwater snail Planorbarius corneus L. experimentally exposed to pentachlorophenol (PCP). Light microscopic histopathological analysis of the PCP-exposed P. corneus revealed significantly enhanced production of the kidney conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…The same effect has been observed in the kidney of bivalves under heavy metal stress (Sulina, 1986(Sulina, , 1989Hemelraad et al, 1990 andRegoli et al, 1992). Also, non metal organic pollutants caused an increase in the number of concretions in the kidneys of the marine prosobranch Littorina littorea and in the freshwater snail Planorbarius corneus (Klobučar et al, 2001). Degeneration of some nephrocytes and hyalinization of fibrous connective tissue were observed in the present study.…”
Section: (A) a Continuous Epithelium Of Columnar Cells The Nephrocytsupporting
confidence: 69%
See 2 more Smart Citations
“…The same effect has been observed in the kidney of bivalves under heavy metal stress (Sulina, 1986(Sulina, , 1989Hemelraad et al, 1990 andRegoli et al, 1992). Also, non metal organic pollutants caused an increase in the number of concretions in the kidneys of the marine prosobranch Littorina littorea and in the freshwater snail Planorbarius corneus (Klobučar et al, 2001). Degeneration of some nephrocytes and hyalinization of fibrous connective tissue were observed in the present study.…”
Section: (A) a Continuous Epithelium Of Columnar Cells The Nephrocytsupporting
confidence: 69%
“…Light microscopic analysis in the present study of the kidney of E. vermiculata showed similarity to some extent to that described for other molluscs as Agriolimax reticulates (Runham and Hunter, 1971); Helix pomatia (Newell and Skelding, 1973); Littorina littrea and Planorbarius corneus (Klobučar et al, 2001). Molluscan kidney consists of a tubule enclosing a luminal cavity derived from the coelom.…”
Section: (A) a Continuous Epithelium Of Columnar Cells The Nephrocytmentioning
confidence: 56%
See 1 more Smart Citation
“…It was suggested that the concretions could be a means of heavy metal detoxification, the metals being added by accretion onto the external layers of the concretion. Experimental exposure of the freshwater snail Planorbius corneus to the pesticide pentachlorophenol induced an increased production and release of these concretions (Klobucar et al 2001). It seems that the stress caused by pollution such as trace metals causes the increase in kidney concretions.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, studies on laboratory cultures of candidate species like P. corneus could provide data for breeding and maintenance conditions. P. corneus and other freshwater snails have been used for decades in ecotoxicological research but mainly on specimens collected shortly prior to the experiments without laboratory culturing (Klobučar et al, 1997(Klobučar et al, , 2001Lajtner et al, 1996Lajtner et al, , 2003Otludil et al, 2004;Pavlica et al, 2000;Špoljar et al, 2005). The aim of this paper is to present the results of analyses on the reproduction and growth of P. corneus over the course of several years of continuous rearing in the laboratory, which was conducted in order to use them as a test organism for partial life-cycle and full life-cycle toxicity testing (Mazuran et al, 1999).…”
Section: Introductionmentioning
confidence: 99%